The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/1747-0080.12652
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition risk screening methods for adults living with severe mental illness: A scoping review

Abstract: Aim: Adults living with severe mental illness experience a greater burden of physical comorbidities and earlier mortality than the general population. Malnutrition, overnutrition, dysphagia, constipation and disordered eating have been observed in this population and can lead to poor nutritional status. Early

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 41 publications
1
20
0
2
Order By: Relevance
“…As described in the introduction, there are no validated nutritional risk screening methods for people with mental disorders ( 9 ). To assess the risk for nutritional deficits, we will use three different nutrition risk scores, additional questions related to the participants' nutritional status and laboratory parameters if they were retrieved during treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As described in the introduction, there are no validated nutritional risk screening methods for people with mental disorders ( 9 ). To assess the risk for nutritional deficits, we will use three different nutrition risk scores, additional questions related to the participants' nutritional status and laboratory parameters if they were retrieved during treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The planning and implementation of effective nutritional interventions in mental healthcare require a valid assessment of patients' nutritional status, challenges and needs. However, to date, no validated nutritional risk screening methods that also consider overnutrition exist for people with mental disorders ( 9 ). Similar to the somatic hospital setting ( 10 ), regular nutritional risk screening should be established in mental healthcare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Phase I, complete versions of the 17 tools identified in the recent scoping review by Hancox et al (2021) were obtained, and individual questions/items were extracted and collated [24]. Each of the 194 questions/items was inductively coded in a consensual procedure by authors AMS and ST.…”
Section: Phase I: Development Of Overarching Domains and Themes Of Interestmentioning
confidence: 99%
“…One method to reduce this gap is the targeted referral of "at-risk" service users to special clinicians, e.g., referral to dietitians when a service user is deemed at risk for over-or undernutrition. A recent scoping review of nutrition screening tools used in mental-health settings found a dearth of targeted and adequately validated tools [24]. The Approaches to Schizophrenia Communication-Self-Report (ASC-SR) Checklist was the only nutrition-risk screening method for overnutrition and undernutrition identified, but this is focusing on side effects of antipsychotic treatment only [25].…”
Section: Introductionmentioning
confidence: 99%